Uncovering the identity of Electronic Markets research through text mining techniques - Nora Nahr; Marikka Heikkilä (Electronic Markets, 2022)
As an established academic journal in the e-commerce and digital platforms fields, Electronic Markets (EM) features a diverse range of topics and occupies a significant role in the information systems field. The study investigates EM's topic diversity over the time period 2009–2020 using a text mining analysis and a bibliometric analysis and identifies 28 cluster groups. The analysis reveals that the top three topics are 1) service quality, 2) blockchain and other shared trust building solutions, their impact and credibility, as well as 3) consumer buying behavior and interactions. EM's core identity lies in a balanced set of core themes that bring technological, business or human/ social perspectives to the research of networked business and digital economy. This includes research on digital and smart services, applications, consumer behavior and business models, as well as technology and e-commerce data. Ethical and sustainability related topics are however still less present in EM.
Keywords: A10; C38; 620; Electronic Markets journal; Core identity; Text mining analysis; Cluster analysis; Unsupervised machine learning; Bibliometric analysis